Neck seatbelt sign suspicion of injury score derived from emergency physician diagnostic imaging practice. (April 2016) - Langdorf, Mark I; Beier, Lancelot; Youseffian, Arthur; Anderson, Craig L; Iqbal, Anum; Kashi, Mayur; Lotfipour, Shahram; Chakravarthy, Bharath
Introduction: Neck abrasion/contusions from seatbelts after motor vehicle collisions may be associated with underlying bony or vascular injury. The decision to order imaging is highly subjective, and the yield is low. To date, there is no objective guidance in the literature regarding which patients need imaging. The aim of this study was to derive a scoring system from physical characteristics of seatbelt contusion photographs, based on emergency physician (EP) decisions to order imaging. Methods: A survey of a convenience sample of practicing and academic EPs, given five photographs of a spectrum of seatbelt contusions and a standard brief patient description. Respondents were asked whether and which imaging they would perform for each photo. Respondents rated photos for overall clinical concern for underlying injury and for concern regarding color, size, depth, texture and location on a five-point Likert scale. Logistic regression to assess associations between these five features and overall clinical concern, and the strength of association between features, overall concern, and decision to image was conducted. Results: Overall, 97 respondents (24% of those surveyed) provided 425 imaging decisions and 95% would image at least one hypothetical patient. However, 40% would not image at least one of the five patients. Decision to image for five photos ranged from 20.0% to 90.6%. Intra-class correlation coefficient for decision to image was fair (0.31, 95% CI 0.13–0.79), indicating variability in practice, and highlighting need for a scoring system. Computed tomography (CT) and CT angiography were used most often for bony and vascular imaging. A 12-point severity scoring system based on location, depth, size and color is proposed. This scale had strong correlation with decision to image (Pearson r = 0.94). Conclusion: Physician practice shows variability in decision to image patients with neck seatbelt contusions after motor vehicle trauma. A proposed severity scoring system may begin to promote evidence based practice.